ASPEK PERFEKTIF DALAM AL-QUR’AN - Setiawan, Rezky Feryansyah; Sanusi, Anwar (Departemen Pendidikan Bahasa Arab, 2019)
The perfective in Arabic is indicated by a form of mÄá¸i verb used to indicate the past time. In the Qur'an there are often verses that describe the future (imperfective) but are contained in the mÄá¸i verb. The research using this qualitative descriptive approach aims to know the meaning contained in the verses contained in the form of the mÄá¸i verb but in the future context. The sample of this study using purposive sampling in the form of verses that contain mÄá¸i verb in it that perpektive and imperfective aspect. The perfective aspect of the verses is inseparable from the influence of the letters that associated with the mÄá¸i verbs and also has implications for meaning and time.